Deliberate practice for retinopathy of prematurity: Retinal laser training using schematic eyes in ophthalmology education - Narisa Rattanalert; Supaporn Tengtrisorn; Phanthipha Wongwai; Atchareeya Wiwatwongwana; Penny Singha; Sirinya Suwannaraj; Thunyaluck Jiwanarom; Warachaya Phanphruk; Parichat Damthongsuk; Dorene F. Balmer (PLoS ONE, 2025)
Skills and confidence in performing high-risk procedures are essential for ensuring safe patient care. Deliberate practice is an instructional model designed to improve performance by engaging trainees in structured, repetitive practice with immediate feedback provided by supervisors. We developed a multifaceted simulation informed by deliberate practice and tested the hypothesis that trainee skills and reported confidence would increase after training. A multicenter prospective study was conducted at three universities in Thailand from July 1, 2023, to June 30, 2024. Sixty ophthalmology trainees participated in an introductory video for self-study and then completed a multiple-choice questionnaire to assess their baseline knowledge of laser indirect ophthalmoscopy for retinopathy of prematurity (LIO-ROP) and guide feedback by supervisors. The participants subsequently performed a simulated LIO-ROP on a schematic eye and received additional feedback based on a scoring rubric. The participants practiced on the schematic eye as much as needed to feel confident in their skills. Mean rubric scores indicative of LIO-ROP skills significantly improved from 2.94 to 3.59 out of 4 (P < 0.001), and the time required for the laser procedure decreased from 17.19 to 15.14 minutes in pre- and post-LIO-ROP practice, respectively. Rubric scores for performing the LIO-ROP on a schematic eye significantly improved across all steps of the procedure between pre- and post-LIO-ROP practice. Reported confidence in performing the LIO-ROP increased by 81.5%. Multifaceted simulated training informed by deliberate practice is a suitable instructional model for enhancing skill performance and confidence among postgraduate residents.